Selling sunshine : surviving teenage motherhood, thriving in luxury real estate, and finally finding my voice / Mary Bonnet. - Bonnet, Mary (HarperCollins Publishers, 2024)
"Fan-favorite star of Netflix’s hit reality series Selling Sunset, Mary Bonnet, tells the deeply personal and inspiring story of her life in and out of the spotlight—from her experience as a teen mom, to surviving personal tragedy and trauma, to building her career as a luxury agent for the most successful brokerage firm in Los Angeles." -- Publisher's website.